X-ray Photoelectron Spectroscopic Study on the Anodic Passivity of Sputterdeposited W-Ta Alloys in 12 M HCl - Bhattarai, Jagadeesh (Nepal Journal of Science and Technology, 2012)
The role of a simultaneous additions of tungsten and tantalum on the anodic passivity of the passive films of the sputter-deposited nanocrystalline W-xTa alloys was studied using immersion tests, electrochemical measurements and X-ray photoelectron spectroscopic (XPS) analysis. The formation of spontaneous passive film on the alloys, which is composed of double oxyhydroxide of tungsten and tantalum ions are responsible for their higher corrosion resistance than those of the alloy-constituting elements in 12 M HCl solution open to air at 30°C. The quantitative surface analysis by XPS is clarified that the improved anodic passivity of the alloys than those of alloy-constituting elements is based on the formation of new anodic passive oxyhydroxide films composed of W6+ and Ta5+ ions. These films have higher protectiveness and stability than those of passive oxyhydroxide films of alloy-constituting elements, that is, oxyhydroxides of hexavalent tungsten and pentavalent tantalum after potentiostatic polarization for 1 h in 12 M HCl. DOI: http://dx.doi.org/10.3126/njst.v12i0.6492 Nepal Journal of Science and Technology 12 (2011) 139-148